2023
DOI: 10.1108/pm-10-2022-0072
|View full text |Cite
|
Sign up to set email alerts
|

Social sustainability under threat: a case of two collapsed buildings in Lagos, Nigeria

Abstract: PurposeHousing provision and the neighbourhood's safety are significant social sustainability concerns. If structural issues are not well checked, housing provision and the neighbourhood's safety may become threatened, especially in Lagos State, Nigeria. Thus, this study aims to investigate the perceived root cause of collapsed buildings at the construction stage using two case studies, its effect on social sustainability aspects and suggested measures to mitigate future happening and enhance achieving social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Yan and Kim (2018) affirmed that occurrence is frequent during construction. Boateng (2020) and Ebekozien et al . (2023a) asserted that several factors could influence building collapse.…”
Section: Literature Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…Yan and Kim (2018) affirmed that occurrence is frequent during construction. Boateng (2020) and Ebekozien et al . (2023a) asserted that several factors could influence building collapse.…”
Section: Literature Reviewmentioning
confidence: 92%
“…After the initially localised let-down, they recommended a design with sufficient load rearrangement capacity. Studies (Alinaitwe and Ekolu, 2014; Moullier, 2015; Boateng, 2020; 2020; Okeke et al ., 2020; Braithwaite, 2021; Ebekozien et al ., 2023a) stated that building collapse is rampant in developing countries and majorly caused by human errors. Moullier (2015) avowed that the pattern of building collapse is more rampant in Kenya's urban locations, as reported by World Bank.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, Ebekozien and colleagues delved into the "Social Sustainability of Building Failures in Lagos, Nigeria: A Structural Health Monitoring Perspective." Utilizing economic analysis and interviews, they aimed to assess the socioeconomic impact of building collapses in Nigeria and the potential contribution of structural health monitoring [7]. The results revealed significant economic and social consequences, but a research gap was identified: a limited understanding of how monitoring systems can effectively mitigate these consequences.…”
Section: IImentioning
confidence: 99%